Parietal Epidural Dermoid Mimicking a Scalp Abscess in an Infant: Case Report - Roka, Yam B; Bajracharya, A; Shrestha, K; Khaniya, S (Journal of Nepal Paediatric Society, 2009)
Scalp masses that involve the scalp or the cranium especially over the parietal bone are uncommon presentation in infants. We report a case of an 8-week old female child who presented with a left parietal scalp mass which had been progressively increasing since birth. CT scan revealed the mass extending into the cranium with underlying bone defect over the parietal area, with medial extension till the sagittal suture. Intraoperatively there was presence of thick white infected flaky material with small tufts of hair which was removed completely till the bone edges and from the epidural space. There was no recurrence postoperatively and the baby was discharged after a week of antibiotics. This case provides an example that simple looking scalp masses in infants and children should be managed with caution to prevent further morbidity. Key words: Dermoid, Scalp abscess doi: 10.3126/jnps.v29i2.2048 J. Nepal Paediatr. Soc. Vol 29, No. 2, pp.98-100